2018
DOI: 10.1002/anie.201806916
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Thermodynamics of Ligand Binding to CsPbBr3 Quantum Dots

Abstract: Cesium lead halide perovskites are an emerging class of quantum dots (QDs) that have shown promise in a variety of applications; however, their properties are highly dependent on their surface chemistry. To this point, the thermodynamics of ligand binding remain unstudied. Herein, H NMR methods were used to quantify the thermodynamics of ligand exchange on CsPbBr QDs. Both oleic acid and oleylamine native ligands dynamically interact with the CsPbBr QD surface, having individual surface densities of 1.2-1.7 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
185
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(200 citation statements)
references
References 21 publications
14
185
1
Order By: Relevance
“…35 In turn, CsPbX 3 (X = Cl, Br, I) nanocrystals display highly dynamic coordination chemistry, 36,37 and their native surface can be exchanged with various cationic and anionic ligands. 38,39,40,41 NaBiE 2 nanocrystals (E = S or Se) adopt a ternary rock salt structure in which mixed Na + /Bi 3+ cation sites are stuffed into the octahedral holes of an fcc arrangement of chalcogenide (E 2-) ions. NaBiS 2 can be thought of as isostructural to PbS, with mixed Na + /Bi 3+ sites replacing Pb 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…35 In turn, CsPbX 3 (X = Cl, Br, I) nanocrystals display highly dynamic coordination chemistry, 36,37 and their native surface can be exchanged with various cationic and anionic ligands. 38,39,40,41 NaBiE 2 nanocrystals (E = S or Se) adopt a ternary rock salt structure in which mixed Na + /Bi 3+ cation sites are stuffed into the octahedral holes of an fcc arrangement of chalcogenide (E 2-) ions. NaBiS 2 can be thought of as isostructural to PbS, with mixed Na + /Bi 3+ sites replacing Pb 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] However, ligand binding to the surface is highly dynamic, which could lead to rapid desorption of the capping ligands, resulting in the formation of undercoordinated lead atoms, which act as surface traps. [20][21][22][23][24][25] Some reports have already shown that postsynthetic thiocyanate surface treatment [26,27] or inorganic passivation via the addition of ZnBr 2 [28] enables efficient trap suppression and a PLQY near unity.…”
mentioning
confidence: 99%
“…The nature of the interaction between the ligand binding group and the nanocrystal surface is crucial to the efficacy and stability of surface defect passivation. [38,39] The length, bulk, and branching of the ligand tail strongly affect the colloidal stability of the nanocrystals and their conductivity when deposited as thin films for electronic devices. [40][41][42] Furthermore, the one-pot nature of the colloidal synthesis means that the impact of purification processes, which are necessary to remove reaction by-products and excesses, must also be considered.…”
Section: Introductionmentioning
confidence: 99%